Departicipation of Youth in Agricultural Sector (Case Study at Delanggu Village, Delanggu, Klaten) - D Dilahur; U Umrotun; P Priyono; Choirul Amin; M. Farid Aminudin (Forum Geografi, 2001)
This study is carried out in Delanggu, Klaten, that has high productivity of rice but undergoing a decrease in the role of the sector of agriculture. The goal of this study is to observe young people departicipation in the sector od agriculture and fators that influence it. The method used is survey method. The population is all of the young people in Delanggu, 1.419 peoples. The sampling uses stratified proporsional quota sampling where respondents are divided into three groups of age, 15-19 years old, 20-24 years old, and 25-29 years old. Every sampling in eah group is taken 5% proportionally, with its homogenates consideration, while the characteristic, which has determined in order to fulfil the number of determined quota in each age group. Collected data is presented in the form of frequency and cross table. Qualitative data analysis uses logical thought, deducyive-inductive, analogy ang comparison, whereas analyzing frequency and cross table uses quantitative data analysis. The use of both analysis is adjusted to the data and goal of the study.